Numerical simulation of partially blocked electrodes under cyclic voltammetry conditions: influence of the block unit geometry on the global electrochemical properties - Chevallier, F; Davies, T; Klymenko, O; Jiang, L; Jones, T; Compton, R (2005)
A general mathematical model for partially blocked electrodes (PBEs) taking into account the finite volume and height of the blocking units has been developed and solved using numerical simulation. The electrochemical behaviour of this model was studied and compared to the common 'flat block' approach in which the blocks are assumed to have zero height to highlight the main differences and explain their origins. © 2004 Elsevier B.V. All rights reserved.